Nigeria's Policy Pathways - International Water Management Institute (International Water Management Institute, 2024)
Join us in Nigeria for Policy Pathways Episode 5! The episode features insight on Nigerian policy coherence from the Director of Agricultural Economics at the University of Port Harcourt, Anthony Onoja, IWMI Senior Researcher Charity Osei-Amponsah, and Minister for Climate Management Michael Adegboye.